Whole-Exome Sequencing Identified Molecular Variants Linked to the Progression of Gastric Precancerous Lesions in Patients from Southwestern Colombia—An Exploratory Approach - Lizeth Mejia-Ortiz; Jovanny Zabaleta; Jone Garai; Luis Eduardo Bravo; Andres Castillo (Gastrointestinal Disorders, 2025)
Background/Objectives: This study aimed to identify molecular variants associated with the progression of gastric precancerous lesions in a follow-up study conducted on patients from Southwestern Colombia. Methods: Whole-exome sequencing (WES) was performed on patients enrolled in the Colombian chemoprevention trial, who were classified into two groups—progression and regression—based on changes in the severity of their gastric precancerous lesions over 16 years of follow-up. The bioinformatics pipeline included steps for quality control, mapping, variant calling, filtering, and annotation. Associations between molecular variants and lesion progression were analyzed using Fisher’s exact test and the Cochran–Armitage trend test. Additionally, functional impact and pathway enrichment analyses were performed for variants that showed significant associations. Results: Thirty-eight molecular variants from thirty-seven participants were associated with the progression of gastric precancerous lesions. These variants were found in tumor suppressor genes like CDKN2A and CDK4, which are involved in cell cycle regulation and apoptosis. Additionally, variants were identified in extracellular matrix regulators such as COL23A1, LAMA2, and TNR. Other noteworthy findings included variants in FLT1, which is linked to VEGF signaling in angiogenesis, and APOB, which is involved in modulating inflammatory responses. Furthermore, alterations in genes associated with the hemostatic system, such as FGA and F5, underscored the connection between hemostasis and carcinogenesis. Conclusions: This exploratory analysis highlighted some molecular variants that may affect the function, structure, and expression of key proteins involved in cancer development, contributing to the progression of gastric precancerous lesions.